The Method of Studying the Ideal and Artistic Characteristics of the Work "Starry Nights" - Safarov Dilshod, (Journal of Artificial Intelligence and Digital Economy, 2024)
In this article, the life and work of Pirimkul Kadyrov, the ideological-artistic features of the work "Starry Nights" are taught in general secondary schools, the educational-educational process is activated, students' ideological, literary-aesthetic it is highlighted that it has great opportunities in solving the task of education.